1998
DOI: 10.2466/pms.1998.86.2.571
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exertion in Simple Reaction Time and Continuous Attention of Sport Participants

Abstract: To investigate the effect of physical exertion on simple reaction time and continuous attention of sport participants, an experiment was conducted with 46 male university students and 12 male cyclists. The subjects were assigned to three experimental and two control groups. The subjects of the experimental groups were asked to perform, following a 5-min, period of warming up, a high intensity exercise protocol for 5 min., on a mechanically braked cycle ergometer (Group A) or a moderate intensity exercise proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
3
11
0
2
Order By: Relevance
“…Tsorbatzoudis et al (36) reported similar results to our own. In this study, simple RT was neither significantly affected by the intensity nor the duration of physical exertion, but a learning effect did appear to be present in both the exercise and control groups.…”
Section: Discussionsupporting
confidence: 91%
“…Tsorbatzoudis et al (36) reported similar results to our own. In this study, simple RT was neither significantly affected by the intensity nor the duration of physical exertion, but a learning effect did appear to be present in both the exercise and control groups.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have reported both positive and negative transfer effects on performance (Adam et al, 1997;Blackwood et al, 1998;Féry et al, 1997;Verger et al, 1998). However, a lack of behavioral effects after physical effort has been reported before (Tsorbatzoudis et al, 1998) and Matsumoto et al (2002) also found the combination of subjective activating effects without behavioral effects. These findings on the one hand indicate that performance is only decreased after great exhaustion; on the other hand the results suggest that task performance does not necessarily increase as a consequence of a higher level of vigilance.…”
Section: Discussionmentioning
confidence: 87%
“…The effects of physical effort on behavioral performance are not clear. Studies have reported no effects (Tsorbatzoudis et al, 1998), negative effects (Kubitz and Pothakos, 1997), positive effects (Adam et al, 1997;Verger et al, 1998), negative effects in chronically fatigued persons (Blackwood et al, 1998), and positive effects after mild exercise, but negative effects after strenuous exercise (Féry et al, 1997). It appears that physical effort may affect performance positively, yet if sustained until sheer exhaustion, physical effort may decrease vigilance.…”
mentioning
confidence: 95%
“…somente mais tarde, alguns estudos enfocaram aspectos do controle motor (13) , investigando as habilidades no esporte relacionadas à percepção de estímulos do ambiente e aspectos subjacentes a este, que, em vista do melhor desempenho de atletas com relação a não-atletas, parecia privilegiada no esporte. muitos dos estudos investigaram indicadores dos mecanismos de processamento central, como antecipação, exploração visual do ambiente, reconhecimento de situações de jogo, entre outros (13,16,18,20) .…”
Section: Introductionunclassified
“…recentes estudos têm demonstrado que atletas possuem um processamento central mais eficiente que não-atletas, provenientes de possíveis facilitações neurais concedidas pela prática esportiva (1,16,20) . Com a prática, o atleta aprende a identificar quais são os estímulos mais adequados e a probabilidade dos mesmos ocorrerem para a tomada de decisão de determinadas respostas motoras (10) .…”
Section: Introductionunclassified